Parental Leave Policies, Intra-household Time Allocations and Children's Human Capital - Bernal, Raquel; Fruttero, Anna (2012)
This paper uses a general equilibrium model of marriage and divorce to assess how public policies on parental leave and leave benefits affect intra-household decision making, family structure, intergenerational mobility, and the distribution of income. The benchmark economy is calibrated to US data to replicate some characteristics relevant to the interaction between the marriage and labor markets. The effects of unpaid leave, paid leave benefits, and mandated leave on human capital investment, distribution of income, and welfare are then analyzed.